9 Micrornas Represent Novel Biological Markers of Coronary Artery Calcification. (6th June 2015) - Howlett, Philippa; Waheed, Abdul; Horton, Alex; Shah, Nikunj; Leatham, Edward; Wu, Huihai; Gerber, Andre; Mahmoudi, Michael
Abstract : Introduction: Conventional risk stratification fails to identify many individuals presenting with major adverse cardiovascular events (MACE). Coronary artery calcification (CAC) is a powerful independent predictor of MACE however its use is limited by radiation and expense. MicroRNAs are non-coding RNAs that regulate transcription and their differential expression is acknowledged to be a hallmark of a number of diseases. We aim to determine if a peripheral blood-based microRNA profile is predictive of the presence and extent of CAC in humans. Methods: Study patients met the following inclusion criteria: attendance for elective cardiac computed tomography; age 18–65 years; no history of coronary artery disease, cardiomyopathy or tachyarrhythmia; normal renal function; no history of diabetes mellitus; no autoimmune disease; no infection; no malignancy. Peripheral venesection was performed and an Agatston score was derived using default software. RNA was extracted using the LeukoLOCK Total RNA Isolation System and stored at –80 o C until Toray's microarray analysis was undertaken. Results: 24 participants were recruited (mean age 54 years; 67% male) and divided into the following categories: [CAC score 0] n = 6; [CAC score 1–10] n = 6; [CAC score 11–100] n = 6; [CAC score > 100] n = 6. Groups were matched according to their baseline characteristics; Table 1 . The Student's t-test was performed between groups. MiR-1181 was significantly down-regulated in all case groups compared to controls: [CAC 1–10] effect size (ES) = 1.76, p = 0.012; [CAC 11–100] ES = 1.74, p = 0.013; [CAC > 100] ES = 3.86, p < 0.01. Furthermore miR-138-2-3p, miR-6816-3p and miR-8059 were expressed less in those with a CAC score > 100 compared to controls (ES = 3, p < 0.001; ES = 2.87, p < 0.001; ES = 2.6, p = 0.001 respectively); Figure 1 . Conclusions: Human blood-based miRNA-1181 appears to predict the presence and extent of CAC. Likewise miRNAs miR-138-2-3p, miR-6816-3p and miR-8059 are differentially expressed in patients with high CAC scores. We plan to validate these findings using quantitative real-time PCR and to test these results in a prospective cohort. Ultimately miRNAs could act as a biomarker for MACE and identifying their associated molecular pathways may explain the mechanisms underpinning CAC.